Potential of Stichopus hermanni as a scaffold material in dental tissue engineering: Potensi Stichopus hermanni sebagai bahan penyangga dalam rekayasa jaringan gigi - Amin, Asmawati; Thalib, Alqarama Mahardhika; Thalib, Bahruddin; Fauzan, Muhammad Fadil; Sambara, Eser Suryanti (Makassar Dental Journal PDGI Makassar, 2025)
This article evaluates Stichopus hermanni as a scaffold for dental tissue engineering, focusing on biocompatibility, osteogenesis, angiogenesis, and immunomodulation. A systematic literature was conducted through PubMed/MEDLINE, Scopus, ScienceDi- rect, Google Scholar, and national databases. Studies were selected using the PICOS framework, covering both in vitro and in vivo research. The results showed that S.hermanni-based scaffolds, either alone or in combination with hydroxyapatite or chito-san, exhibited high biocompatibility, non-toxicity, increased osteogenic markers (CD44, IL-10, osteocalcin, bFGF), angiogenesis, and woven bone formation. This scaffold also reduced osteoclast activity through immunomodulatory effects. It was concluded that S.hermanni has strong potential as a biomaterial scaffold in dental tissue engineering, supporting the safe and effective re-generation of hard and soft tissues.